Persepsi Pengunjung Terhadap Miniatur Hutan Hujan Tropis (MH2T) Kalimantan Selatan: Visitors Perception on the Tropical Rain Forest Miniature (MH2T) of South Borneo - Yasinta Nur Shiba; Arfa Agustina Rezekiah; Wahyuni Ilham (HUTAN TROPIKA, 2022)
One of the green open spaces in the city of Banjarbaru is Tropical Rain Forest Miniature (MH2T) of South Borneo. MH2T is the only miniature rainforest in South Borneo, which was directly approved by the President of Republic Indonesia, Joko Widodo. MH2T built on an area of 90 hectares. This place also used as a place to travel by enjoying natural scenery, exercising and other activities. For the development of MH2T, perceptions from visitors is needed. It can be seen from the perception of visitors to tourist attractions. The method used to determine the perception is questionnaires and interviews. The results of these questionnaires and interviews, it was found that visitors were satisfird with the existence of MH2T and felt that MH2T had an impact on their lives. According to visitors, MH2T management is also good, in terms of cleanliness, security, accessibility and the infrastructure is good and well maintained. Kata kunci (Keywords): MH2T, Perception, Management, Interview, Likert